The Effect of hand grip strength, wrist flexibility, and hand-eye coordination on forehand drive skills - Nur Septian Maulana, Hernawan, Taufik Rihatno (Gladi : Jurnal Ilmu Keolahragaan, 2023)
This research aimed to cognize the effect of hand grip strength, wrist flexibility, and hand-eye coordination on forehand drive skills in badminton extracurricular students in senior high schools in Jatiasih sub-district. The research method used was a survey method by using test and measurement techniques. The data was analyzed with path analysis. The population was determined in students who followed badminton extracurricular badminton in senior high schools in Jatiasih sub-district as many as 60 students. Sampling technique used was total sampling so that sample numbered 60 people. Instrument hand grip strength test, flexibility test, hand eye coordination test, and forehand drive test in badminton. The instrument was compiled by researchers and consulted with Sports Test and Measurement expert. The result showed that (1) there was a direct effect of hand grip strength (X1) on hand-eye coordination (X3). (2) There was a direct effect of wrist flexibility (X2) on the variable hand-eye coordination (X3). (3) There was a direct effect of hand grip strength (X3) on forehand drive skills (Y). (4) There was a direct effect of wrist flexibility (X2) on forehand drive skills (Y). (5) There was a direct effect of hand-eye coordination (X3) on forehand drive skills (Y). (6) There was an indirect effect of hand grip strength (X1) on forehand drive skills (Y) through hand-eye coordination (X3). (7) There was an indirect effect of wrist flexibility (X2) on forehand drive skills through hand-eye coordination (X3).